The archaeometric, formal and stylistic analysis of a black-glazed fish-plate from the National Museum in Poznań - Głuszek, Inga; Krueger, Michał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
This paper presents the results of the XRF, formal and stylistic analyses of a black-glaze fish-plate from the National Museum in Poznań. A non-invasive portable X-ray fluorescence spectrometer (pXRF) has been used to determine the chemical composition of the plate. Analysis of the shape and decoration provided data on the chronology, typology and provenance of the vessel. The obtained results were used to determine the possible region of the fish-plate’s production. The form of the fish-plate represents features characteristic for the early stage of Italian black-glaze production, which is combination of Athenian traditions with new solutions in terms of proportion and shape. The analysis of X-ray fluorescence spectrometry data and comparative studies with already known results of the Italian black glaze pottery chemical analyses allowed the fish-plate to be identified as an example of the Campania A group from ancient Naples workshops, dated to the second half of the 4th century BC.
Keywords: black-glaze pottery; X-ray fluorescence spectroscopy; provenience; multivariate analyses; museum collections